Climate Data Guide Spurs Discovery and Understanding. (26th March 2013) - Schneider, David P.; Deser, Clara; Fasullo, John; Trenberth, Kevin E.
Abstract : Highly accurate and stable observations—beyond those provided by routine weather monitoring—are essential for understanding the behavior of the climate system, developing and validating Earth system models, and attributing extreme weather events and long‐term trends to causes [ National Research Council, 2012; Trenberth et al ., 2013]. In parallel with an exploding volume of climate data, ready access to data in user‐friendly formats is important to an expanding number and increasing diversity of individuals worldwide across public, private, and academic sectors [ Overpeck et al ., 2011].